On the reserves of the infant mortality reduction in Russia - A.A. Baranov; V.Yu. Albitsky; A.G. A.G. Ilyin ("Paediatrician" Publishers LLC, 2006)
<span style="font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: RU; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">(Voprosy sovremennoi pediatrii = Current pediatrics. 2006; 5 (5): 5-7)